IMPROVING VEHICLE TAX COMPLIANCE THROUGH HR COMPETENCE AND PUBLIC SERVICE PROMOTION: EVIDENCE FROM RIAU ISLANDS PROVINCE - Ronni Yanto; Tibrani Tibrani; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Tax compliance remains a critical challenge for local governments, particularly in the domain of vehicle taxation which contributes significantly to regional revenues. This study aims to examine the extent to which human resource (HR) competence and public service promotion influence vehicle tax compliance in the Riau Islands. Employing a quantitative approach with survey, we collected 92 respondents from taxpayers and local revenue office employees, the research utilizes structural equation modeling (SEM) to analyze causal relationships among variables. The findings reveal that HR competence, encompassing professional knowledge, administrative skills, and service orientation, exerts a significant positive effect on taxpayer compliance. Similarly, public service promotion-delivered through information campaigns, digital platforms, and community outreach-enhances taxpayers’ awareness, trust, and willingness to fulfill their obligations. Furthermore, the study highlights the combined effect of HR competence and service promotion strengthens compliance behavior by fostering a sense of procedural fairness and improving the perceived quality of government services. These results underscore the importance of strengthening human resource capacity and implementing innovative service promotion strategies as key policy instruments to improve vehicle tax compliance. The study contributes both theoretically and practically: it enriches the discourse on fiscal policy and public administration, while offering evidence-based recommendations for local governments to optimize tax revenue management.